Manajemen Proyek Inovasi Mahasiswa (Studi Kasus Ecostove Dalam Program Pembinaan Wirausaha P2mw 2024) - Nurjanah, Erni (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2025)
This study aims to describe the project management process of student innovation through a case study of the development of EcoStove, a portable stove powered by used cooking oil, within the framework of the 2024 Student Entrepreneurship Development Program (P2MW). EcoStove was initiated by a team of Digital Business students in response to household waste issues and the market demand for eco-friendly outdoor equipment. The research employs a qualitative descriptive approach using a case study method. Data were collected through participatory observation, documentation of activity reports, and reflections from students and supervising lecturers over a five-month implementation period. The results show that students successfully applied project management principles systematically, covering planning, prototype development, field testing, digital promotion, limited product sales, and final evaluation. In addition to delivering a useful and environmentally friendly product, student involvement in the project fostered the development of key entrepreneurial competencies, including critical thinking, communication, teamwork, and environmental awareness. Key success factors include financial support from the P2MW grant, active guidance from supervising lecturers, and academic recognition through credit conversion aligned with the Merdeka Belajar Kampus Merdeka (MBKM) policy. This study concludes that eco-innovation-based entrepreneurship projects serve as effective learning models that not only nurture entrepreneurial character but also promote social and environmental contributions. These findings offer theoretical implications for the advancement of experiential learning and eco-innovation literature in entrepreneurship education, as well as practical implications for higher education institutions in designing project-based learning programs that emphasize sustainability and entrepreneurial competence.